Applied spirituality and sustainable development policy - Singh, Naresh; Bhatnagar, Divya (Emerald Publishing Limited, 2023)
The fundamental cause of many of the global challenges we are currently facing is our disconnection from ourselves, our fellow humans, other beings, and our planet. We have consistently failed to recognize the inner consciousness that dictates our relationships and decisions, an awareness that could be the first step toward humanity's quest to set civilization on a more sustainable trajectory. Rooted in both secular spirituality and scientific evidence, Applied Spirituality and Sustainable Development Policy articulates a new model of sustainable development that is not just based on narrow definitions of GDP and economic growth, but that includes and even forefronts social and environmental development and inner transformation of human beings. Drawing on fields from physics to public policy, 18 pioneering authors discuss: A distillation of the spiritual gems at the core of the world's major religions, including Indic and Buddhist philosophy Root-cause analyses of major sustainable development policy challenges like climate change Connections between spirituality and law, and how our legal frameworks can reflect these values The need for leaders to understand their spiritual nature in order to be authentic and transformative in their leadership styles. Recognizing a global need for healing, this book rejuvenates how we think about development and nurture our innate spirituality, and challenges us to shift our collective mindset from one of having to one of being.